The Evolving Role of Cyclin D1 as a Biological Surrogate for Differentiation and Hormone Receptor Status in Breast Carcinoma - Abhishek Verma; Manisha Sharma; Manas Madan; Karamjit Singh Gill (Annals of Pathology and Laboratory Medicine, 2026)
Background: Breast cancer in India often presents with aggressive characteristics and high mortality. Cyclin D1 is a critical regulator of the G1/S phase transition and is emerging as a significant biomarker.Methods: A cross-sectional study of 52 mastectomy specimens was conducted. Histological grading (Nottingham modification) and immunohistochemical (IHC) staining for ER, PR, Her2Neu, and Cyclin D1 were performed. Result: Cyclin D1 positivity was observed in 51.9% of cases. A highly significant positive correlation was found between Cyclin D1 expression and ER status (p < 0.001) and PR status (p < 0.001). Conversely, Cyclin D1 showed a strong inverse correlation with histological grade (p = 0.002); Grade III tumors were significantly more likely to be Cyclin D1 negative. No significant correlation was found with age, tumor size, or lymph node status.Conclusion: Cyclin D1 serves as a molecular hallmark of differentiation in breast cancer, being robustly maintained in hormone-dependent, lower-grade tumors and lost in aggressive, de-differentiated phenotypes.